Commentary on the effects of hypoxia on energy substrate use during exercise - Young, A. J.; Margolis, L. M.; Pasiakos, S. M. (Journal of the International Society of Sports Nutrition, 2019)
A recently published meta-analysis in this journal analyzed findings from studies comparing substrate use during exercise at the same relative intensity (i.e., % VO2max) in normoxic and hypoxic conditions. The primary conclusion was that hypoxia had no consistent effects on the contribution of carbohydrate oxidation to total energy expenditure. However, findings from studies comparing exercise at the same absolute intensity in normoxic as hypoxic conditions were not considered in the meta-analysis. Assessment of substrate oxidation using matched absolute intensity leads to different conclusions regarding hypoxic effects on fuel use during exercise, and that experimental model, (i.e., comparing responses to exercise at matched absolute intensity) has more practical application for developing nutritional recommendations for high-altitude sojourners. This commentary will discuss those differences.